Effect of Storage Time on Some Quality Characteristics of Dried Kumquat Slices by Different Drying Methods - Demet YILDIZ TURGUT; Ayhan TOPUZ (Yüzüncü Yıl Üniversitesi Tarim Bilimleri Dergisi)
In this study, dried kumquat slices by different drying methods were stored at room conditions for 4 months and the product quality and stability were investigated during storage. For this purpose, the kumquat slices were dried by four drying methods including hot air, vacuum, ultrasound assisted osmotic pre-drying with hot air, and microwave assisted hot air drying with pretreatment by water blanching and without pretreatment. The moisture content and water activity values of dried kumquat slices increased during storage, and the lowest increase was determined in samples dried by hot air drying method without pretreatment. In general, L*, b*, chroma, hue angle values decreased, while a* and TRD values increased in all dried samples at the end of the storage. HMF values were ranged from 0.39 to 46.79 mg/kg during storage. It was observed that the ascorbic acid content of dried samples lost 28.36-75.61% during storage period. As a result of the study, it has been determined that drying of kumquat slices by without pretreatment is more suitable in terms of the examined quality properties during storage for 4 months.